Kesulitan Siswa Kelas 3 Dalam Pemecahan Soal Cerita Matematika Materi Bangun Datar Di Sekolah MIN 9 Medan - July Antika; Rustam Rustam; Lailatun Nur Kamalia Siregar (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The research that has been carried out is entitled "Difficulties of Grade 3 Students in Solving Math Story Problems on Flat Shape Material at MIN 9 Medan School" with the background that students at this school have problems with solving math word problems. Among them are students not being able to determine what things they have to do first in solving story problems, the accuracy of matching objects and the ability of students to draw conclusions from the work done by students and relate it to the initial problem to be solved. This study aims to determine the ability of grade 3 students in solving word problems, the completion stage, and identify the difficulties experienced by grade 3 students at MIN 9 Medan. The research methodology uses a qualitative approach. The sampling technique is based on the criteria set by the researcher. The informants in this study were all 30 grade 3 students at MIN 9 Medan. Retrieval of research data used in this thesis, namely interviews. The data processing tool in this study is descriptive qualitative analysis. The results showed that: 1) Students' difficulties in solving word problems at the understanding stage were difficulties in identifying the question keywords, students' difficulties at the planning stage were difficulties in transforming the question sentences into mathematical models, students' difficulties at the plan implementation stage were difficult calculations influenced by the students' ability in multiplication and division as well as mastery of the concept of measurement material, the difficulty of calculating is characterized by calculation errors made by students, the difficulty at the review stage is in the form of difficulty writing concluding sentences, 2) The factors causing the difficulties experienced by students consist of four causal factors namely personal factors of students, factors of giving assistance, factors of mastery of concepts and factors of student perceptions, 3) Efforts that can be made by the teacher to reduce student difficulties, namely identifying problems with difficulties experienced by students, making story questions using communicative language, increasing practice questions stories, implementing cooperative learning, contextual learning, providing individual guidance, providing motivation and rewards and using learning media.